Integration System Of Web Based And SMS Gateway For Information System Of Tracer Study - Endyk Noviyantono; . Aidil (Bandar Lampung University (UBL), 2012)
Tracer Study today now required to become an official activity carried out by the entire campus in Indonesia to carry out supervision of all activities of the alumni. Observations on the date of graduation from college, a long wait after getting a job for the first time, information about the location currently occupied jobs, wages earned, as well as the input to the campus about the demands of jobs.Information systems are made with the integration between the use of web media that can later be used by the Alumni to update the data itself, as well as media use SMS Gateway which will provide another convenience for the Alumni to give her information to the college with the last condition.Information systems design and integration of web based and sms gateway is started from the analysis of the system to be constructed, database and relational database design that required, the design of interfaces for the integration of the two media are created, and testing sistem to be use, using a blackbox test and alpha test for completeness of the information that will provide.Login and password on a web media for Alumni will be given after a student to register using SMS Gateway. With the mobile phone-based registration is also ultimately to be a connectivity campus with Alumni, information about the alumni meeting, current information about the college and job information to the alumni who did not get a job or wanting to to move a new job.